A Comprehensive Review of Biogas Sector for Electric Power Generation in Pakistan - Shaukat, Neelofar; Khan, Bilal; Khan, Taimur; Younis, Muhammad Naeem; Faris, Najam ul; Javed, Aqib; Iqbal, Muhammad Naeem (PSM Biological Research, 2016)
This review study is directed towards the establishment of commercial biogas sector for electric power generation in Pakistan. Pakistan is facing severe electric power crisis because of huge mismatch between supply and demand of electric power generation. Major issues lies at generation side as a consequence of poor infrastructure, depleting nature of conventional fuel resources. Keeping in view the Pakistan’s agriculture base and environmental concerns we focus on biogas sector for electric power generation. The marked increase of 3.7% is observed in livestock sector of Pakistan according to economic survey of Pakistan 2012-2013. The aforementioned increase of livestock sector results in 1140 million dung production. Therefore, due to environmental concerns and energy crisis of Pakistan we need to utilize all waste and manure from livestock sector in an efficient way. The transformation process of manure and waste in to methane gas is called Biogas .This methane gas can be utilized as a fuel for domestic and industrial purpose. Therefore, biogas will act as an alternative, sustainable and renewable energy resource. We focus on KPK province for visiting the installed biogas plants and then further analysis the data provided by PCRET (Pakistan Council of Renewable energies technologies) for whole country. The aforementioned analysis clearly illustrated that there is a pronounced potential for commercial biogas sector for mitigating energy crisis in Pakistan.